Respostas
respondido por:
15
f(x)=ax+b
f(-3)=-7 --> -7=a(-3)+b --> -7=-3a+b
f(1)=5 --> 5=a(1)+b --> 5=a+b
5=a+b --> a=5-b
-7=-3a+b --> -7=-3(5-b)+b --> -7=-15+3b+b -->15-7=4b --> 8=4b --> b=8/4 --> b=2
a=5-b --> a=5-(2) --> a=3
f(x)=ax+b
f(x)=3x+2
Renato.
f(-3)=-7 --> -7=a(-3)+b --> -7=-3a+b
f(1)=5 --> 5=a(1)+b --> 5=a+b
5=a+b --> a=5-b
-7=-3a+b --> -7=-3(5-b)+b --> -7=-15+3b+b -->15-7=4b --> 8=4b --> b=8/4 --> b=2
a=5-b --> a=5-(2) --> a=3
f(x)=ax+b
f(x)=3x+2
Renato.
respondido por:
14
(1,5) ;(-3,-7)
y=ax+b
vamos ÷(-1) a 1° , vamos resolver o sistema pela adição
cancela o y e soma
como
y=3x+2
y=ax+b
vamos ÷(-1) a 1° , vamos resolver o sistema pela adição
cancela o y e soma
como
y=3x+2
Anônimo:
♥‿♥
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás